2x平方-1=6x
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 13:13:15
2x平方-1=6x2x平方-1=6x2x平方-1=6x2x²-1=6x移项2x²-6x-1=0用公式法解a=2,b=-6,c=-1△=b²-4ac=(-6)²-
2x平方-1=6x
2x平方-1=6x
2x平方-1=6x
2x²-1=6x 移项
2x²-6x-1=0 用公式法解
a=2 ,b=-6 ,c=-1
△=b²-4ac
=(-6)²-4×2×(-1)
=36+8
=44
√△=√44=2√11
x=(-b±√△)/(2a)
=(6±2√11)/4
=(3±√11)/2
x1=(3+√11)/2
x2=(3-√11)/2
=(x平方+5x+4)(x平方+5x+6)+1 =(x平方+5x+4)平方+2(x平方+5x+4)+1
1/(x-2)-6/(x平方-4)=12x/(x-1平方)=1/(x平方-x)
x平方-x+1=x平方-x分之6
6x+2x的平方-3x+x的平方+1,其中x=5
(x平方+x)(x平方+x-2)=-1 用换元法
2x平方-1=6x
先化简,再求值:[(3x-3y)/(y平方-x平方)+(x平方-2xy+y平方)/(x平方-y平方)-(x平方-x+6)/(x+2)]/(x+y),其中x=3,y=1
如何解(X平方 X 1)/(X平方 1) (2X平方 X 2)/(X平方 X 1)=19/6
x平方=14x;(x+6)平方=51;x平方-2x=4;3x平方-5x+1=0
(1-x/3-x)平方除以x平方-6x+9/9-x平方*1/x平方-2x+1
(7/2x平方+6x)-(11-2x平方/9-x平方)+2,其中x=-1
(7/2x平方+6x)-(11-2x平方/9-x平方)+2,其中x=-1
x/x平方-x+2=2x/x+1
2X平方+6X-1=3 X平方+3X-2=?
分式方程:x的平方+2x-6/x的平方+2x=1
x的平方+2x-x的平方+2x分之6=1
(x的平方+y的平方+1)(x的平方+y的平方+2)=6
①x平方-( )x+1=(x-1)平方 ②x平方+4x+( )=(x+ )平方③2x平方+6x+( )=2(x+二分之三)平方